Graphene Oxide: Strategies for Synthesis, Reduction and Frontier Applications - Singh, D (Royal Society of Chemistry, 2016)
Till now, several innovative methods have been developed for the synthesis of graphene materials including mechanical exfoliation, epitaxial growth by chemical vapor deposition, chemical reduction of graphite oxide, liquid-phase exfoliation, arc discharge of graphite, in situ electron beam irradiation, epitaxial growth on SiC, thermal fusion, laser reduction of polymers sheets and unzipping of carbon nanotubes etc. Generally large scale graphene nanosheets are reliably synthesized utilizing other forms of graphene-based novel materials, including graphene oxide (GO), exfoliated graphite oxide (by thermal and microwave), and reduced graphene oxide. The degree of GO reduction and number of graphene layers are minimized mainly by applying two approaches via chemical or thermal treatments. The promising and excellent properties together with the ease of processability and chemical functionalization makes graphene based materials especially GO, ideal candidates for incorporation into a variety of advanced functional materials. Chemical functionalization of graphene can be easily achieved, by the introduction of various functional groups. These functional groups help to control and manipulate the graphene surfaces and help to tune the properties of the resulting hybrid materials. Importantly, graphene and its derivatives GO, have been explored in a wide range of applications, such as energy generation/storage, optical devices, electronic and photonic devices, drug delivery, clean energy, and chemical/bio sensors. In this review article, we have incorporated a general introduction of GO, its synthesis, reduction and some selected frontier applications. © 2016 The Royal Society of Chemistry.